Supernumerary Teeth in Indian Children: A Survey of 300 Cases - Amita Sharma; Varun Pratap Singh (Hindawi Limited, 2012)
The aim of this investigation was to study children with supernumerary teeth who visited the Department of Pedodontics and Preventive Dentistry, Government Dental College and Hospital, Rohtak, Haryana, India. Only children with supernumerary teeth were included in the study while patients having supernumerary teeth with associated syndromes were excluded. Supernumeraries were detected by clinical and radiographic examination. The results indicated that males were affected more than females with a sex ratio of 2.9 : 1. Single supernumerary tooth was seen in 79% of the patients, 20% had double, and 1% had three or more supernumeraries. Premaxillary supernumeraries accounted for 93.8% of the cases. Conical shaped supernumerary teeth were the most common type (59.7%). Majority of supernumeraries remained unerupted (65%). Fusion of supernumerary tooth with a regular tooth was observed in 4% of the patients. Talon cusp, an associated dental anomaly, was seen in 5% of the cases. Simultaneous hypodontia occurred in 2.3% of patients with supernumeraries.